Multi-omics approaches to study platelet mechanisms. (April 2023) - Solari, Fiorella A.; Krahn, Daniel; Swieringa, Frauke; Verhelst, Steven; Rassaf, Tienush; Tasdogan, Alpaslan; Zahedi, Rene P.; Lorenz, Kristina; Renné, Thomas; Heemskerk, Johan W.M.; Sickmann, Albert
Abstract: Platelets are small anucleate cell fragments (2–4 μm in diameter) in the blood, which play an essential role in thrombosis and hemostasis. Genetic or acquired platelet dysfunctions are linked to bleeding, increased risk of thromboembolic events and cardiovascular diseases. Advanced proteomic approaches may pave the way to a better understanding of the roles of platelets in hemostasis, and pathophysiological processes such as inflammation, metastatic spread and thrombosis. Further insights into the molecular biology of platelets are crucial to aid drug development and identify diagnostic markers of platelet activation. Platelet activation is known to be an extremely rapid process and involves multiple post-translational mechanisms at sub second time scale, including proteolysis and phosphorylation. Multi-omics technologies and biochemical approaches can be exploited to precisely probe and define these posttranslational pathways. Notably, the absence of a nucleus in platelets significantly reduces the number of present proteins, simplifying mass spectrometry-based proteomics and metabolomics approaches.